Safeguarding patients from technology-facilitated abuse in clinical settings: A narrative review. - Isabel Straw; Leonie Tanczer (PLOS Digital Health)
Safeguarding vulnerable patients is a key responsibility of healthcare professionals. Yet, existing clinical and patient management protocols are outdated as they do not address the emerging threats of technology-facilitated abuse. The latter describes the misuse of digital systems such as smartphones or other Internet-connected devices to monitor, control and intimidate individuals. The lack of attention given to how technology-facilitated abuse may affect patients in their lives, can result in clinicians failing to protect vulnerable patients and may affect their care in several unexpected ways. We attempt to address this gap by evaluating the literature that is available to healthcare practitioners working with patients impacted by digitally enabled forms of harm. A literature search was carried out between September 2021 and January 2022, in which three academic databases were probed using strings of relevant search terms, returning a total of 59 articles for full text review. The articles were appraised according to three criteria: (a) the focus on technology-facilitated abuse; (b) the relevance to clinical settings; and (c) the role of healthcare practitioners in safeguarding. Of the 59 articles, 17 articles met at least one criterion and only one article met all three criteria. We drew additional information from the grey literature to identify areas for improvement in medical settings and at-risk patient groups. Technology-facilitated abuse concerns healthcare professionals from the point of consultation to the point of discharge, as a result clinicians need to be equipped with the tools to identify and address these harms at any stage of the patient's journey. In this article, we offer recommendations for further research within different medical subspecialities and highlight areas requiring policy development in clinical environments.